Cybersecurity in smart grid - Gao, Jingquan (Nanyang Technological University, 2020)
With the background that advanced meter infrastructure highly developed, the cybersecurity become an import and valuable topic in the smart grid. This dissertation builds server and client with gRPC frame work in the physical device. To explore how the server performs at the poor condition of network resource and system resource by SYN-flood attack and limiting the CPU usage. The experiment indicates that the frequency of message transmission decrease at both situation while DoS attack causes the packet loss additionally.